KOMUNIKASI KRISIS HUMAS KEMENTERIAN AGAMA DALAM MENGKLARIFIKASI PEMBERITAAN CNNINDONESIA.COM DAN DETIK.COM UNTUK MENJAGA REPUTASI LEMBAGA - Sri Lestari Nengsih; Yuliandre Darwis (Jurnal Ranah Komunikasi, 2022)
This study summarizes the government's public relations activities carried out by the Ministry of Religion Public Relations at the time of reporting on the statement of the Minister of Religion on February 23, 2022. The activities carried out by public relations are then analyzed using crisis communication theory by utilizing digital platforms. The use of digital platforms such as social media can benefit the Ministry of Religion's PR to communicate in times of crisis because it is transparent, involves the public, and is more interactive. This journal aims to provide comprehensive information on the use of digital platforms by the ministry of religion in times of crisis by clarifying the framing of news framing online media cnnindonesia and detik.com .